Diseño e implementación de un módulo didáctico de control de motores eléctricos, Valle Jequetepeque 2022 - Banda Terán, Luis Javier (2023)
In the present investigation the design and implementation of a didactic module for the control of electric motors was carried out, since the E.A.P. of Mechanical Engineering of the National University of Trujillo - Filial Valle Jequetepeque, where currently there is no such equipment to complement the studies of the courses of electric machines, machines that are considered necessary and fundamental in the formation of future professionals of Mechanical Engineering. First, we proceeded to design this module, considering the syllabus of the courses of electrical machines and the inherent requirements for its operation and safety. Three proposals were presented, of which the most economical, safest and most versatile according to the design matrix was chosen. The option chosen consisted of a metallic structure, two modular blocks, electrical components, measuring instruments and 1 HP and 0.5 HP electric motors. The structure was subjected to a static simulation in CAD software where the structural weight of the module that was obtained was equal to 174.39 Kg was added an external load of 450 Kg in the structural tubes that make up the module, obtaining as main result a minimum safety factor of 4.907, also calculations were made to select the electrical components having as nominal current of selection 9 A, from this current were oversized thinking in future modifications. Safety parameters were taken as the use of male banana plug connectors that isolate the connection tips, also terminals were used for the connection of the electrical components to the female banana plugs, the soldering points with tin that we have present were covered with insulating tape thus avoiding that they are exposed. Subsequently, the components were assembled in the corresponding modular blocks. At the end of the assembly, the module was tested for operation, verifying that all the components and electrical machines are operative. For this purpose, it was verified that during the start-up of the 0.5 HP motor, the current and voltage were 1.1 A and 380 V, respectively, and the 1 HP motor, the current and voltage were 2 A and 380 V, respectively. During the operation of the module, there was no significant risk to the person operating the module. In addition, a laboratory guide was prepared for the electrical machine courses, consisting of 22 practical exercises. The manufacturing cost was S/. 8 070.59, while the cost of a module with similar requirements is S/. 93 000, resulting in a saving of S/. 84 929.41.